All Days 2010
DOI: 10.4043/20758-ms
|View full text |Cite
|
Sign up to set email alerts
|

Installation of Two Prototype Deep Penetrating Anchors at the Gjoa Field in the North Sea

Abstract: The installation of two full-sized 80ton Deep Penetrating Anchors (DPA™) in August 2009 marked the end of a technological qualification process for this free-fall anchor concept for mooring of offshore floating structures. These anchors are 13m in length with four meter wide fins and were installated at the Gjøa Field in the North Sea off the West coast of Norway. Maximum pullout capacity is approximately 700tons. The anchors will be used by the mobile drilling rig (MODU) TransOcean Searcher for drilling and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 1 publication
2
28
0
1
Order By: Relevance
“…This gap remains somewhat constant ( $ 8.0%) as the impact velocity increases from 20 m/s to 30 m/s. A similar concept has been used at the Vøring Plateau, Troll Field and Gjøa Field in the North Sea (Lieng et al, 2010;Sturm et al, 2011) and in the Gulf of Mexico (Wodehouse et al, 2007;Zimmerman et al, 2009). Hossain et al (2014) provided a summary of these field tests.…”
Section: Effect Of Reference Strain Rate (_ γ Ref )mentioning
confidence: 94%
See 1 more Smart Citation
“…This gap remains somewhat constant ( $ 8.0%) as the impact velocity increases from 20 m/s to 30 m/s. A similar concept has been used at the Vøring Plateau, Troll Field and Gjøa Field in the North Sea (Lieng et al, 2010;Sturm et al, 2011) and in the Gulf of Mexico (Wodehouse et al, 2007;Zimmerman et al, 2009). Hossain et al (2014) provided a summary of these field tests.…”
Section: Effect Of Reference Strain Rate (_ γ Ref )mentioning
confidence: 94%
“…In this analysis, values for the various parameters were adopted as follows: C d ¼0.63 (Lieng et al, 1999(Lieng et al, , 2000(Lieng et al, , 2010Sturm et al, 2011;O'Loughlin et al, 2013), n ¼1.0, N c,bA ¼13.56, N c,bF ¼ 7.5, η¼1.0, β ¼0.1, δ rem ¼1/S t ¼1/3, and ξ 95 ¼ 20. For the frictional resistance, R f2 was taken as 2R f1 from the previous reports (Einav and Randolph, 2006;Chow et al, 2014;Steiner et al, 2014).…”
Section: Extended Bearing Resistance Methodsmentioning
confidence: 99%
“…In order to select realistic anchor and soil parameters, a survey was carried out through reported case histories and field trials at various locations in the Campos Basin, offshore Brazil; Vøring Plateau, Troll Field and Gjøa Field in the North Sea, off the Western coast of Norway (Medeiros, 2002;de Araujo et al, 2004;Brandão et al, 2006;Zimmerman et al, 2009;Lieng et al, 2010) and offshore geotechnical characterisation report (Argiolas and Rosas, 2003;Randolph, 2004). Hossain et al (2014) provided a summary of these field tests.…”
Section: Geometry and Parametersmentioning
confidence: 99%
“…A new hybrid anchoring system, referred to as the dynamically embedded plate anchor (DEPLA), combines the capacity advantages of vertically loaded anchors (Murff et al 2005;Gaudin et al 2006;Wong et al 2012) with the installation advantages of dynamically installed anchors (Medeiros 2001;Zimmerman et al 2009;Lieng et al 2010). The DEPLA comprises a removable central shaft or "follower" that may be fully or partially solid and a set of four flukes (see Fig.…”
Section: Introductionmentioning
confidence: 98%
“…Predicting the final embedment of the DEPLA after free-fall is complicated by the very high penetration velocities, as this significantly enhances the available shear resistance and introduces inertial drag resistance. As the velocity of dynamically installed anchors when they impact the seabed is typically between 10 and 30 m/s (Lieng et al 2010), for a typical anchor with a shaft diameter of about 1 m, the strain rates in the soil during installation are three orders of magnitude higher than that in a vane test (0.029 s −1 , Einav and Randolph 2006) and seven orders of magnitude higher than the standard laboratory testing rate of 1%/h (2.8 × 10 −6 s −1 ). O'Loughlin et al (2013a) showed that, for anchor geometries similar to the DEPLA in normally consolidated clay, inertial drag resistance dominates for embedment depths up to 0.84 times the anchor length.…”
Section: Introductionmentioning
confidence: 99%